Disparities in Women’s Knowledge of Cervical Cancer Early Detection in Sungai Rangas Village - Vena Marisa; Fitri Ayatul Azlina; Rieh Firdausi (FORIKES, 2026)
In Indonesia, the burden of cervical cancer continues to rise, with low screening coverage contributing to delayed diagnosis and preventable deaths. Early detection through screening methods such as Visual Inspection with Acetic Acid (VIA) and Pap smear is essential; however, national coverage remains far below the recommended target. Knowledge deficits among women have been identified as a key barrier to participation in early detection programs. This study aimed to identify the level of knowledge among women regarding early detection of cervical cancer in Sungai Rangas Village, Martapura Barat District. A descriptive quantitative design was employed, and the study was conducted in June 2024. The population consisted of 153 women of reproductive age who had engaged in sexual intercourse and had never undergone cervical cancer screening. Using the Slovin formula and consecutive sampling, 115 respondents were recruited through a door‑to‑door approach across three neighborhood units. Data were collected using a validated and reliable questionnaire comprising 14 multiple‑choice items on cervical cancer and early detection. Validity coefficients ranged from r = 0.353 to r = 0.9707, exceeding the critical value of r = 0.3246, and the reliability coefficient was 0.986. Data were analyzed descriptively to summarize respondent characteristics and knowledge levels, with results presented in tabular form. The findings showed that most respondents were aged 20–30 years, had completed elementary education, were not employed, and primarily received information from healthcare workers. Knowledge levels indicated that 57.4% of women demonstrated good knowledge regarding early detection of cervical cancer, while 42.6% exhibited poor knowledge. These results highlight persistent gaps in awareness that may contribute to low screening uptake in the community. In conclusion, although more than half of the respondents demonstrated adequate knowledge, a substantial proportion still lacked essential understanding of cervical cancer and its early detection methods.Keywords: cervical cancer, early detection, knowledge, women of reproductive age, screening, Indonesia